Bimbingan Islami melalui Kegiatan Tayamum pada Lansia Muslim di Panti Tresna Werdha Hargo Dedali - Annisa Bela Vianty; Azizah Al Faizah; Cindy Deffianisa Azhari; Ragwan Albaar (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2023)
Guidance for the elderly is an important aspect in caring for individual welfare and development in old age. Guidance aims to help seniors understand themselves, improve their quality of life, and overcome challenges they may face at this stage of life. Understanding that prayer is an obligation in Islam is very important, and many elderly people face difficulties or challenges in observing it. One of the conditions for valid prayer is ablution, whereas most elderly people neglect prayer because they are prevented from performing ablution due to their physical condition, such as having a stroke, not being able to maintain ablution easily, and having sore limbs when acting. In order for prayers to continue to be carried out, for elderly people who have difficulty performing ablution, they can use tayamum as a substitute for ablution to perform the prayer service. This research focuses on the stages of tayamum applied to the elderly. The research method used in this research is qualitative, with data collection techniques in the form of observation, interviews and documentation. The research subjects were elderly Muslims who lived in the Hargo Dedali nursing home in Surabaya. The results of this research show that there are elderly people who can carry out the stages of tayamum correctly, but there are elderly people who cannot do it because they are senile and forgetful and because they are physically unable to do so. Islamic guidance through tayamum activities has significant harmony in supporting the spiritual development of the elderly.